CLAY – A VEHICLE OF MEMORY - Basarab, Vlad (Design/Arts/Culture, 2023)
Through my ceramic work and my experience in working with clay in various parts of the world, I look at how clay and ceramics have been forms of communication and are means of transmitting memory. I found in clay’s geologic transformations and in the human interventions it underwent, a metaphor to comment on both fragility and permanence of the human condition, as well as on the different perceptions of time and memory. Giving form out of clay is like writing, composing new meaning from a large database, yet it is empowering when you dig your own clay to know that you are the first human to touch it and are free to make anything you want out of it. My aim for the artwork that I produce is to generate a thought process in regards to how memory is transmitted and oftentimes altered, how accurate information is in general.